2013
DOI: 10.1017/s1368980013000700
|View full text |Cite
|
Sign up to set email alerts
|

Is breakfast skipping associated with physical activity among US adolescents? A cross-sectional study of adolescents aged 12–19 years, National Health and Nutrition Examination Survey (NHANES)

Abstract: Objective: To examine the association between breakfast skipping and physical activity among US adolescents aged 12-19 years. Design: A cross-sectional study of nationally representative 2007-2008 National Health and Nutrition Examination Survey (NHANES) data. Setting: Breakfast skipping was assessed by two 24 h dietary recalls. Physical activity was self-reported by participants and classified based on meeting national recommendations for physical activity for the appropriate age group. Multiple logistic regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 46 publications
3
16
1
Order By: Relevance
“…In line with our findings, a study conducted in adolescents from 41 countries who were not skipping breakfast reported slightly increased odds of being physically active in comparison to breakfast skippers . On the contrary, a study of a sample of US adolescents did not find an association between breakfast skipping and meeting PA guidelines, in both sexes . Furthermore, a study among adolescents from 10 European cities revealed that breakfast consumption was not associated with measured or self‐reported PA .…”
Section: Discussionsupporting
confidence: 86%
“…In line with our findings, a study conducted in adolescents from 41 countries who were not skipping breakfast reported slightly increased odds of being physically active in comparison to breakfast skippers . On the contrary, a study of a sample of US adolescents did not find an association between breakfast skipping and meeting PA guidelines, in both sexes . Furthermore, a study among adolescents from 10 European cities revealed that breakfast consumption was not associated with measured or self‐reported PA .…”
Section: Discussionsupporting
confidence: 86%
“…This is especially important because breakfast consumption also decreases in adolescence. 50 Lastly, consistent with existing research, 6,14,18 our results showed that screen time negatively affects PA in that more hours spent in front of the television or the computer means less time for PA. PA and obesity prevention programs should continue to discourage excessive screen time among school-aged children.…”
Section: Physical Activitysupporting
confidence: 89%
“…Children who eat breakfast more often also engage in PA more frequently. Although a few studies previously found that daily breakfast was not significantly associated with PA, breakfast consumption has also been regarded as a protective factor for obesity and has been linked to longer PA, and our findings lean toward this direction. PA intervention programs should thus consider targeting to increase breakfast consumption among school‐aged children.…”
Section: Discussioncontrasting
confidence: 67%
“…Unlike other studies that found adolescents with normal BMI engage in physical activity more than underweight or overweight, this study showed lower physical activity being executed in underweight, normal, and overweight adolescents. 25 A higher level of physical activity was indeed reported in the overweight group but the intensity was still much lower.…”
Section: Discussionmentioning
confidence: 85%